A sea of debt law and economic life in the western Indian Ocean, 1780-1950 - Bishara, Fahad Ahmad (Cambridge University Press, 2017)
In this innovative legal history of economic life in the Western Indian Ocean, Bishara examines the transformations of Islamic law and Islamicate commercial practices during the emergence of modern capitalism in the region. This study examines the Indian Ocean from Oman to India and East Africa over an extended period of time, drawing together the histories of commerce, law and empire in a sophisticated, original and richly textured history of capitalism in the Islamic world.